The water skater genus Gerris Fabricius (Hemiptera: Heteroptera: Gerridae) in Vietnam, with the description of a new species - Duc, Tran Anh; Polhemus, J. T. (Zootaxa, 2012)
The water skater genus Gerris of Vietnam is reviewed, with a key to species provided. Gerris (s.str.) curvus sp. n. fromsouthern Vietnam is described. The discovery of this species greatly extends the southernmost distributional range of the genus. Two other species, Gerris (s.str.) latiabdominis and Gerris (Macrogerris) gracilicornis, are first records for Vietnam.